OPTIMALISASI RUTE PENDISTRIBUSIAN BUKU DARI PERPUSTAKAAN DAERAH SALATIGA KE SMA DAN SMK NEGERI DENGAN ALGORITMA PRIM - Moufya Fattan Ghifara; Muhammad Ilham Chasanudin; Azza An Nafisah; Muhamad Gani Rohman (REALISTIC: Journal of Education Mathematics and Science, 2024)
This research aims to optimize the process of distributing books from the Salatiga City Regional Library to state high schools and state vocational high schools in the Salatiga area. Distribution of books from regional libraries to schools is an important effort to improve the quality of education by providing access to adequate learning resources. However, the main problem faced is determining the optimal distribution route with the shortest and fastest distance and time. To solve this problem, the researcher attempted this research by applying the Prim algorithm to find the minimum spanning tree in a distribution network which is modeled as a weighted graph. Distance and travel time data collection via the Google Maps application. Data on distance and travel time between locations is used to build a distribution network model. Next, Prim's algorithm is applied to find the shortest and fastest route. The research results show that the application of the Prim algorithm can optimize the book distribution route from the Salatiga City Library to these schools. The shortest and fastest route found is able to reduce travel distance and delivery time, thereby increasing the efficiency of the distribution process both in terms of cost and time. In this way, the quality of book distribution services can be improved significantly. These findings can be a reference for the Salatiga City Library and schools in the area to improve and optimize the book distribution process in the future.